Influence of thermal stress on a coral-associated bacterial community - Diaz, Leomir A. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2016)
The coral holobiont includes the coral animal, its dinoflagellate symbionts, and its associated microbial community. Symbionts complement the host enome by providing metabolic precursors that the coral itself cannot synthesize. In exchange, the host provides its sybionts with material that they can catabolize and feed into their own biosynthetic pathways. The inability to maintain these symbiotic interactions when challenged by an environmental stressor, such as increased sea surface temperature, leads to a decline in coral health that is observed as a rise in the incidence of cora bleaching and coral disease.In this study, we examine the effect of elevated water temperature on the natural microbial community associated with the outer mucus layer and tissues of the coral, Acropora digitifera. Denaturing gradient gel electrophoresis and high-throughout sequencing of the 15S rRNA V4 hypervariable region revealed that prolonged exposure to high temperature causes a shift in the diversity of the coral microbial community. Notably, there is an increase in the population of bacteria ften found associated with diseased and stressed corals, such as Vibrionales in the mucus and alteromonadales in the tissue. In addition, we found that exposure elevated water temperature causes a change in the community of nitrogen fixing bacteria that are abundant in the coral mucus. These chages may correlat with shifts in the metabolic function of the coral holobiont and may have detrimental effects on the health and resilience of the coral.Taken together, our findings highlight the impac of elevated seawater temperatur on the bacterial composition and diversity in corals and the effects of this on holobiont metabolism.